Chest X‐ray severity score Brixia: From marker of early COVID‐19 infection to predictor of worse outcome in internal medicine wards. (21st November 2022) - Carbone, Federico; Casaleggio, Alessandro; Fiannacca, Martina; Borda, Fabio; Ministrini, Stefano; Vischi, Giulia; Carpaneto, Valeria; Sobrero, Matteo; Monti, Chiara; De Stefano, Daria; Saccomanno, Benedetta; Massone, Marcella; et al.
Abstract :